Permai Park Inn promotional activities: a study on its sales promotion / Syahrul Hezrin Mahmud - Mahmud, Syahrul Hezrin (1998)
The hospitality industry (hotel) is cyclical, going through big upswings and big downswings. During the economic down turn , hotels can lose a lot of money especially in term of fixed costs. As the impact from economic down turn, the hotel room occupancy rate has declined tremendously compared to the previous years. In order to overcome the problem they are trying to invest heavily in promotional activities especially in term of sales promotion. Therefore, this research paper will emphasize on Permai Park Inn promotional activities especially in term of sales promotion. This research will reveal the effectiveness of sales promotion in improving the sales performance. This research also will find out the aspect of promotional activities in general. The aim of this research paper is to present the ability of the researcher to implement the marketing theories under the actual situation This research paper will present the findings and practical ideas in order to improve the topic under study.